Team project facilitates language learning - Shokri N.M. (Elsevier Ltd, 2023)
This study focuses on a classroom device used - a project-based approach - that integrates language and soft skills simultaneously. The participants for this study are 60 students of foundation (engineering).This study is descriptive and exploratory in nature which the researcher wants to explore whether team project activity can promote the frequent use of English language, practice learners' strategies, and boost learners' self-confidence. It adopts a quantitative method by gauging students' feedback through administering questionnaire. The analysis will look into the percentage of agreement towards the advantages of the team project as a classroom device to promote communicative skills among students. 2010 Published by Elsevier Ltd.